2021
DOI: 10.3390/ijerph182413210
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gamification on the Benefits of Student Response Systems in Learning of Human Anatomy: Three Experimental Studies

Abstract: This paper presents three experiments to assess the impact of gamifying an audience response system on the perceptions and educational performance of students. An audience response system called SIDRA (Immediate Audience Response System in Spanish) and two audience response systems with gamification features, R-G-SIDRA (gamified SIDRA with ranking) and RB-G-SIDRA (gamified SIDRA with ranking and badges), were used in a General and Descriptive Human Anatomy course. Students participated in an empirical study. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 93 publications
0
3
0
1
Order By: Relevance
“…The research findings revealed that the use of gamification is effective in students' learning, which is aligned with the findings of the study by López-Jiménez et al They investigated the effect of gamification on students' learning in the Anatomy course to find out the effects of three student learning systems: expression, participation, and motivation. The results of López-Jiménez and colleagues study showed that students who used the game to learn the course performed better academically compared to the control group (12).…”
Section: Discussionmentioning
confidence: 98%
“…The research findings revealed that the use of gamification is effective in students' learning, which is aligned with the findings of the study by López-Jiménez et al They investigated the effect of gamification on students' learning in the Anatomy course to find out the effects of three student learning systems: expression, participation, and motivation. The results of López-Jiménez and colleagues study showed that students who used the game to learn the course performed better academically compared to the control group (12).…”
Section: Discussionmentioning
confidence: 98%
“…Notably, observation and drawing have been found to significantly enhance the competence of anatomy students, enabling them to recall memorized images and redraw them on paper in the absence of the object, and to identify inaccuracies when compared to illustrations from an anatomy atlas (Reid et al., 2019). The inclusion of gamification using response systems and quiz‐games in the experimental treatment may have contributed to the observed effect of higher CNS, as previous studies have found that these resources increase satisfaction, engagement, and motivation to participate in the classroom when exposed to gamified learning experiences (López‐Jiménez et al., 2021). Moreover, quiz‐games have shown positive effects on achievement and engagement both in class and as a revision tool prior to assessment in higher education teaching of the anatomical sciences (Wilkinson, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…AS, Oslo, Norway) or Quizizz (Quizizz Inc, Bangalore, India), plays a pivotal role in motivating and guiding students, offering valuable insights into their progress, and helping identify areas for improvement (Ismail et al., 2019). These gamified audience response systems have been found to significantly improve academic performance, satisfaction, engagement, and motivation to participate in the classroom compared to non‐gamified systems (López‐Jiménez et al., 2021). Therefore, it seems possible to improve the basic psychological needs addressed by SDT through gamification.…”
Section: Introductionmentioning
confidence: 99%
“…The next largest genre of articles (five in total) explored the use of gaming in medical education in a general sense. These articles covered the following three topics: benefits and pitfalls of incorporating gaming into medical education (López-Jiménez et al, 2021;Maheu-Cadotte et al, 2021;Nevin et al, 2014), student attitudes towards gaming (Kron et al, 2010), and creating a framework to design and build effective games to support medical-related education (Olszewski & Wolbrink, 2017). There were three papers focusing on pharmacyrelated issues.…”
Section: Health and Medicine-level 1 Clustermentioning
confidence: 99%